Simultaneous parametric optimization of micro-EDM drilling of brass C360 using Taguchi based grey relation analysis - Kumar, Pranav (Array, 2021)
Micro-EDM (Electro Discharge Machining) is widely used for precision manufacturing and drilling micro-holes in materials used in fuel nozzles, micro sensors and robots, surgical instruments, turbines etc. Present paper deals with drilling common C360 brass components by micro-machining and optimizing the process parameter using a hybrid approach of design of experiments (DoE) and grey relation analysis (GRA) concept. The three process responses considered are material removal rate (MRR), tool wear rate (TWR) and taper in drilled hole while the four selected controllable process parameters are capacitance(C), voltage(V), feed rate(f) and rotational speed of electrode (N). Significance of input factors on each response is analyzed with the help of a 24 full factorial by conducting 16 experiments at two levels for factors. Optimum levels of robustness for each process response are established through Taguchi"s S/N ratio. A combined grey relation grade is applied to find the process levels conducive for optimizing MRR and TWR simultaneously.